Cash Receipt and Disbursement Control System: Sistem Pengendalian Penerimaan Dan Pengeluaran Kas - Mar’atus Solihah; Heri Widodo (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the cash receipts and disbursements control system (study PO Watukosek Trans 2018-2019). This research method uses qualitative. Data collection is doing by interview. Meanwhile, for observation and documentation involving many crew employees who work in PO (Otobus Company). Activities in data analysis in this study are data collection, data reduction, data display, and conclusion drawing/verification. Based on the analysis and discussion in this study, it is found that the cash receipts control system at the Watukosek Trans Autobus Company (PO) can be said to be quite good. However, there are still some principles and elements of internal control that have not been fulfilled. The cash disbursement control system at the Watukosek Trans Autobus Company (PO) can be said to be quite good. One of the advantages is that the cash receipt system does not involve many functions. Highlights: This study focuses on evaluating the cash receipts and disbursements control system at Watukosek Trans Autobus Company (PO) during the period of 2018-2019. Qualitative research method was used, with data collection conducted through interviews, observation, and documentation involving crew employees. The findings reveal that while the cash control systems are relatively good, there are still some shortcomings in meeting the principles and elements of internal control, highlighting the need for further improvements in the organization's financial processes. Keywords: cash receipts, disbursements control system, qualitative research, PO Watukosek Trans, internal control.